Analisis Kecemasan Belajar Siswa SMP pada Pembelajaran Matematika - Dyah Haerunnisa; Adi Ihsan Imami (Program Studi Pendidikan Matematika, Universitas Majalengka, 2022)
Some students' views about mathematics, there are students who think that mathematics is difficult, causing students to feel afraid and uneasy when learning mathematics. Feelings of fear and restlessness are part of mathematical anxiety. This study aims to determine the level of mathematical anxiety experienced by junior high school students. The research subjects were 37 seventh grade students junior high school in Klari. This type of research is descriptive research with a qualitative approach. The instrument used is a questionnaire which contains 32 statements, where each statement contains 4 aspects of mathematical anxiety. Data on students' mathematical anxiety scores were processed and grouped into five categories, namely: very high, high, medium, low, and very low. Then 5 students were selected, where each student represented each category to be analyzed descriptive from the answers to the questionnaire that had been given. The results showed, 3 students were in the category of very high anxiety level, 5 students were in the category of high mathematical anxiety level, 18 students were in the category of moderate anxiety level category, 8 students were included in the category of low anxiety level and 3 students had very low anxiety level. Thus, it can be seen that the average level of mathematical anxiety experienced by junior high school students is moderate.